2013
DOI: 10.1089/acm.2012.0639
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Adverse Events in China: A Glimpse of Historical and Contextual Aspects

Abstract: The article by He and colleagues, ''Adverse Events Following Acupuncture: A Systematic Review of the Chinese Literature for the Years 1956-2010'' is an important and timely contribution. In this commentary, the article is reviewed and issues are highlighted about how to interpret and contextualize the results of their study. While their review has been well performed, certain areas have been identified where the results may be inaccurate due to problems in the reporting of original incidents. For example, pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“… 9 For example, acupuncture-associated hepatitis B outbreaks were reported in UK, 11 19 Jerusalem 20 and USA 21 between 1970 and 1990. Although there was no such report in China, 22 23 considering the fact that China had a moderate-to-high risk of hepatitis B infection compared to many Western countries, 24 the real situation might be similar in China. 23 Along with the use of single-use disposal needles, infection is no longer the major concern with regard to acupuncture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 For example, acupuncture-associated hepatitis B outbreaks were reported in UK, 11 19 Jerusalem 20 and USA 21 between 1970 and 1990. Although there was no such report in China, 22 23 considering the fact that China had a moderate-to-high risk of hepatitis B infection compared to many Western countries, 24 the real situation might be similar in China. 23 Along with the use of single-use disposal needles, infection is no longer the major concern with regard to acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no such report in China, 22 23 considering the fact that China had a moderate-to-high risk of hepatitis B infection compared to many Western countries, 24 the real situation might be similar in China. 23 Along with the use of single-use disposal needles, infection is no longer the major concern with regard to acupuncture. A number of large surveys on the safety of acupuncture were conducted recently, mainly in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…There were more adverse events in the control group (98 in the control group and 29 in the intervention group). Adverse events in the intervention group included painful sensation (11 cases), ecchymosis (nine cases), flushing (five cases), and itchy sensation after needle withdrawal (four cases) which are common adverse events seen after needle penetration and acupressure [ 41 , 42 ]. In the control group, adverse events that included dry mouth (75 cases), dry skin and desquamation (17 cases), and gastrointestinal discomfort (six cases) are also common adverse events following topical benzoyl peroxide and retinoid treatment [ 4 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 , 12 ] However, as acupuncture is a procedure involving needle insertion into the body, there is controversy as to whether mild pain and mild bleeding after treatment should be regarded as AEs. [ 13 , 14 ] Hence, the reporting criteria for AEs in previous prospective studies have been inconsistent. One study has reported any incidence of bleeding to be an AE of acupuncture treatment.…”
Section: Introductionmentioning
confidence: 99%